EMPLOYMENT IN THE REGION ACCORDING TO QUALIFICATION FIELD - Galina V. Leonidova; Kseniya A. Ustinova (Высшее образование в России, 2016)
The article shows the relevance of studying the issues related to the mismatch between the education system and labor market, particularly employment out of qualification field. The study draws attention to the parameters that determine this process including performance, compliance with special abilities and inclinations, work experience for the last year, sphere related to specialty. The study shows the importance of professional self-improvement for the majority of students, and reveals that an increase in the educational level leads to an increase in this aspiration. A positive decision on employment in qualification field is more likely to be taken under the conditions of good academic performance and greater correspondence between abilities, aptitudes and future profession. The study reveals that employment intention depends on the type of employment and occupation: a positive result is more likely to be achieved among military, engineering and technical personnel engaged in socially-oriented fields and management. Furthermore, in case of the smallest gaps between the existing and desired directions of professional training, average wages in the majority of cases will be higher (except for socially-oriented fields).